Masculinized Male Chest Contouring: Creating the Armor Plate - Mowlavi, Arian (Aesthet Surg J Open Forum, 2019)
Male patients are routinely consulted regarding dislike of their chest appearance. To date, majority of patients have desired elimination of their feminine-appearing breast, termed gynecomastia. These patients have associated their overweight body image, with the femininity of their breasts as presented by fullness and roundedness of their breasts and subsequently have desired maximal flattening of their breast. We present a new set of patients who desire a more muscular-appearing chest than a gynecomastia repair that is interposed on a chiseled abdominal contour. In contrast to the former set of patients, these patients desire bulking of their breasts with a bolder-appearing armor plate look. We present an alternative to traditional gynecomastia repair which involves a novel approach to chest contouring creating a flat, yet bold, pentagonal-shaped breast with linear borders utilizing both fat and gland removal as well as strategic fat grafting back into the chest. We present a novel protocol to create an armor plate male chest appearance as an alternative to traditional gynecomastia contouring. All patients treated to date demonstrate a muscular-appearing chest that is harmonious on an interposed masculine-appearing abdomen.